Sistema de información integrado y publicación de contenidos educativos para la gestión y difusión de trabajos de titulación. - Malla Sánchez, Jorge Luis (2015)
The following project is a technological contribution, due to the use of software on a web environment that will allow us to manage great quantities of information in an order way, decentralized and well distributed about certain certification project that have been developed in the Area of Energy, Industry and Non-Renewable Natural Resources (AEIRNNR) from the National University of Loja (UNL), as well as to provide teachers and students consulting services in real time lapse, and also to spread all the investigations that take place with an essay certification for students, teachers and researchers. In order to develop the software the methodology used was carefully selected with ICONIX which unifies a set of orientation and methods and objects, with one whole objective which is to include the whole cycle life of the project; this offers support from the UML, which is an iterative and incremental process, as well as to publish educational content, this was developed on ontologies supported with the right methodology used, METHONTOLOGY which includes three steps like, Specification, Conceptualization and Implementation. The platform developed a software which is JAVA 7, and also design patters were used (FAÇADE, DTO, DAO, SESSION FAÇADE,) tools (NETBEANS, GLASFISH, VIRTUOSO, OPEN, POSTDEGRES) technologies, techniques and frameworks (JSF, JPA, CDI, Primefaces, Maven, EJB, Apache Jena, Linked Data) We managed to develop software that will be a support for all careers at UNL, if the authorities agree on it, but the principal objective is to add it on the Career of Information and Technology like a pilot plan.